Avaliação de concepções ambientais em alunos do ensino médio: um estudo de caso Bauru/SP - Cardoso, Christopher de Andrade (2017)
Currently, the environmental issues have been given prominence in virtually all spheres of society, especially among the different levels of education. Given this premise, these are high in discussions within schools and universities, however, many of these concepts covered are unknown or little understood by the student universe. This research developed instruments that were applied in students 3rd year of High School, with the intention of understanding about the conceptions of the environmental conservation of these, against some areas. The research was attended by 193 students from five public school classes and four private school classes. Was developed a socioeconomic and a questionnaire structured with questions adapted of vestibular on issues of ecology, environmental education, genetics, deforestation and reforestation. As a proposal to revise or oven teach concepts required in the questions, the students participated in a lecture and a playful activity with the game Environmental Cards. In a last phase the same questionnaire was reapplied to verify if didactic activities were successful. It was observed that in the application of the questionnaire the students considerably reduced (by about 70%) the filling of the alternatives wrong/unknown. The students obtained an average of 51% hit on first application of the questionnaire and 61% hit on reapplication. The classes were submitted to normality test Shapiro-wilk (k samples) resulting in normal distribution. Performance comparisons were performed by the ANOVA fallowed by the test Tukey, for comparison of average rightness between classes. Finally, the test was performed t which compared the first and second applications in each class, presenting these significant statistical difference (p<0.05). The game Environmental Cards obtained in acceptance of 96.98% of the students, considered that the game facilitates at learning. Was identified, in general, the students have little knowledge of concepts that can form citizens aware of acting in favor of environmental conservation, as soon as a playful game can generate greater income from knowledge and attention in the classroom, in order to not only educate, but to pass citizenship principles